How to measure the accessibility maturity of organizations—A survey on accessibility maturity models for higher education - Auer, Nadine; Kalemba, Samira; Stormer, Christin; Boehm, Ann-Katrin; Cetin, Hakan; Gutjahr, Anja; Neumann, Franziska; Kersken, Verena; Weber, Gerhard; Zimmermann, Gottfried (Frontiers in Computer Science, 2023)
Maturity models are increasingly used to advance the processes of organizations, including Higher Education Institutions. In this paper, we review existing maturity models to analyze and optimize the accessibility of organizations are reviewed. Therefore, we conducted a systematic literature research in the databases Web of Science, IEEE Xplore, BASE, ACM, and Google Scholar, resulting in 13 different maturity models. An additional web search on maturity models for accessibility found another 12 maturity models that were we added to the results. Finally, we analyzed the 25 maturity models were analyzed in more detail, specifically on the indicators that each maturity model uses to measure accessibility. The most frequent indicators were “responsibility”, “competences & training”, and “monitoring”, with differences in the frequencies when separated by target group. Out of the 25 maturity models found, only 6 focused on Higher Education Institutions. None of the existing maturity models focuses on teaching and learning of accessibility explicitly.